2014
DOI: 10.1097/olq.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Epidemiology of the Syphilis Epidemic in Toronto, Canada

Abstract: Toronto's syphilis epidemic is mature. Response, resources, and intervention activities should target core and noncore areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…It also joins recent work in translational science, which seeks to improve our understanding of STI transmission dynamics and translate these findings into specific recommendations for the targeted control of STIs (33, 42). Future research should focus on providing a better understanding of the stability of the identified venues and identifying other important features of venues which distinguish places with ongoing transmission.…”
Section: Discussionmentioning
confidence: 92%
“…It also joins recent work in translational science, which seeks to improve our understanding of STI transmission dynamics and translate these findings into specific recommendations for the targeted control of STIs (33, 42). Future research should focus on providing a better understanding of the stability of the identified venues and identifying other important features of venues which distinguish places with ongoing transmission.…”
Section: Discussionmentioning
confidence: 92%
“…Existe uma íntima relação entre a infecção por sífilis com comportamentos de maior vulnerabilidade, caracterizados principalmente pela exposição a múltiplas parcerias sexuais, ausência de preservativo nas relações, presença de outras ISTs (24) .…”
Section: Descriptoresunclassified
“…Investigation of syphilis incidence requires consideration of re-infection to fully characterize the patterns of population-level transmission and to design interventions. New syphilis cases among HIV co-infected men commonly have a past history of previous syphilis infection [ 8 , 14 , 15 ]. Epidemiological characterization of the rate of first versus subsequent syphilis infections could help to determine to what extent syphilis epidemics are concentrated in core groups experiencing repeated infections.…”
Section: Introductionmentioning
confidence: 99%